Interpretasi Makna Lagu Boku No Taiyou Karya AKB48 - Kanuruhan, Putu Dyah; Budiana, I Made; Lestari, Ni Putu Candra (UNIVERSITAS SERAMBI MEKKAH, 2024)
This research examines the interpretation of the meaning of the song Boku no Taiyou from the Japanese idol group AKB48. The lyrics of this song are the object of research because they are considered to reflect values and interpretations of meaning that have relevance to people's lives. Semiotic theory is used to explore the hidden meanings in song lyrics. The theory used to analyze the lyrics uses two theoretical approaches, the semiotic theory by Michael Riffaterre and the moral theory by Nurgiyantoro. Michael Riffaterre's approach provides a view of how signs are used in creating hidden meanings and messages. Meanwhile, Nurgiyantoro's moral theory is used to analyze the moral messages contained in the song lyrics, especially in the context of relationships between individuals and the importance of support in achieving dreams. The analysis results provide an in-depth understanding of how AKB48 uses figurative language and moral messages in their song lyrics to convey positive values and encouragement to their listeners.